2012
DOI: 10.1063/1.4765705
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of a high-resolution candidate detector for prostate time-of-flight positron emission tomography

Abstract: We report on the measurements performed using a (22)Na source on a detector element for a magnetic resonance imaging-compatible time-of-flight-positron emission tomography endorectal prostate probe, with depth-of-interaction sensitivity. It is made from a LYSO scintillator crystal, wrapped with Lumirror, readout at both ends by means of silicon photomultipliers. With a detailed description of the data analysis procedure, we show that our results point to a 400 ps coincidence resolving time and, at the same tim… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 28 publications
(40 reference statements)
0
6
0
Order By: Relevance
“…The SiPM is a rather new photodetector featuring, among other properties, very good photodetection efficiency, intrinsic signal amplification of the order of 10 6 , low-voltage operation (30-70 V), good energy resolution, superior timing properties. Its main disadvantage, namely the few millimeter small size, turns into an advantage for TOF-PET as it makes possible to set up arrays of high performance tiny detectors [33], [34], [35].…”
Section: Time Of Flight Positron Emission Tomography (Tof-pet)mentioning
confidence: 99%
See 1 more Smart Citation
“…The SiPM is a rather new photodetector featuring, among other properties, very good photodetection efficiency, intrinsic signal amplification of the order of 10 6 , low-voltage operation (30-70 V), good energy resolution, superior timing properties. Its main disadvantage, namely the few millimeter small size, turns into an advantage for TOF-PET as it makes possible to set up arrays of high performance tiny detectors [33], [34], [35].…”
Section: Time Of Flight Positron Emission Tomography (Tof-pet)mentioning
confidence: 99%
“…Figure 20 explains why it is important to correct the parallax effect by determining event by event the Depth Of Interaction (DOI) in the detectors, in order to make the most of their spatial resolution. An example of miniature detectors for TOF-PET [33], [34], [35] is based on 1.5 mm ´ 1.5 mm ´ 10 mm LYSO scintillators, each one read out by means of two SiPMs (Figure 21). In such a configuration, if a gamma-gamma coincidence is detected for instance in detectors #k and #m, the eight quantities…”
Section: Time Of Flight Positron Emission Tomography (Tof-pet)mentioning
confidence: 99%
“…Recent LSO and LYSO based detectors have exhibited resolutions larger than 200 ps [37]- [39]. However, simulations have shown that a resolution of around 100 ps is achievable if both sides of a LYSO crystal are coupled to a SiPM matrix [40].…”
Section: Tdc Specificationsmentioning
confidence: 99%
“…The detector was exposed to a moderated AmBe neutron source, and the data were analyzed using the same technique as described in [10,11] that also allows to reconstruct the impact position on the strip. The total light spectrum, shown in Fig.…”
Section: Scintillators For Neutron Detectionmentioning
confidence: 99%